Characterising a SOX2+ OLIG2+ glioma stem cell using Crispr-engineered fluorescent reporters in primary patient-derived GBM and DIPG cells. (12th October 2019) - Finlay, Jack; Hallou, Clement; Dewari, Pooran; Pollard, Steven; Pathania, Manav; Bulstrode, Harry; Rowitch, David
Abstract: Malignant glioma can be understood as a cancer stem cell disease. There is strong evidence that expression of a core set of neural stem cell master regulators is necessary and sufficient for tumour initiation in both adult and childhood disease subtypes, and across a range of underlying mutation signatures and expression profiles. We hypothesise that a double positive SOX2+ OLIG2+ progenitor is the cancer stem cell in H3K27M diffuse intrinsic pontine glioma (DIPG) and adult glioblastoma (GBM) alike. We present expression data in 4 patient-derived cell lines (2 adult GBM, 2 DIPG) in vitro and in a defined mutation mouse model of the H3K27M disease, demonstrating high expression levels of SOX2 and OLIG2 in serum-free culture and especially in the invasive tumour. We then demonstrate derivation of patient-derived human dual reporter lines, using a CRISPR targeting approach to add fluorescent reporters at the endogenous SOX2 and OLIG2 loci. With these tools, we aim to characterise the tumour-initiating potential of the SOX2+ OLIG2+ fraction. We further aim to identify cell surface markers whose expression is driven by this transcription program and which might represent targets for novel molecular therapies.